Neonatal Gastrointestinal Emergencies - Alatas, Fatima Safira (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: Neonatal gastrointestinal emergencies refer to a set of life-threatening conditions affecting the digestive system of a newborn within the first 28 days of life and often associated with high morbidity and mortality. As such, these conditions require immediate and accurate diagnosis as well as proper treatment to optimize the outcomes of these patients. This condition has the potential to obstruct the flow of gastric content leading to vomiting, failure to thrive, and electrolyte imbalances. Discussion: Gastrointestinal obstruction is one of the most common conditions causing emergency condition in neonates. This condition may occur anywhere between the upper part of gastrointestinal tract to the lower gastrointestinal tract. In most cases of neonatal gastrointestinal emergencies, patients almost always present with vomiting that may be bilious or non-bilious. Furthermore, persistent vomiting may also lead to a more severe consequences such as hypovolemic shock and electrolyte imbalances. Therefore, clinicians are expected to address this problem early while also working to find the underlying etiologies of neonatal vomiting. On the other hand, gastrointestinal bleeding is often an alarming sign that indicates a possible emergency condition in neonates. However, some non-emergency condition such as swallowed maternal blood and cow's milk allergy can also result in gastrointestinal bleeding in neonates. Conclusion: Given the critical time window and the vulnerability of the neonate population, the proper identification and prompt treatment of neonatal gastrointestinal emergencies is crucial to minimize morbidity and mortality. Multidisciplinary management with neonatologists, pediatric surgeons, radiologists, and nursing staff working closely together can provide the best possible outcomes.